Dynamics of magnetized string cosmological model in f(R,T) gravity theory - Ram S.; Chandel S. (My University, 2025)
The spatially homogeneous and anisotropic Bianchi type V cosmological solutions of massive string have been investigated in the presence of a magnetic field within the framework of f(R,T) gravity theory. With the help of the hybrid expansion law for the average scale factor a cosmological model is obtained. It is shown that the universe exhibits transition from deceleration to acceleration. We also find that Bianchi type V model is anisotropic at the early stage of evolution of the universe and become isotropic for large time. We also check the stability of solutions through cosmological perturbation. The physical and kinematical behaviors of the model are also studied. © 2014, Springer Science+Business Media Dordrecht.